Community adaptation to temperature explains abrupt soil bacterial community shift along a geothermal gradient on Iceland - Weedon, James T.; Baath, Erland; Rijkers, Ruud; Reischke, Stephanie; Sigurdsson, Bjarni D.; Oddsdottir, Edda; van Hal, Jurgen; Aerts, Rien; Janssens, Ivan; van Bodegom, Peter M. (Soil Biology and Biochemistry, 2023)
Abstract: Understanding how and why soil microbial communities respond to temperature changes is important for un-derstanding the drivers of microbial distribution and abundance. Studying soil microbe responses to warming is often made difficult by concurrent warming effects on soil and vegetation and by a limited number of warming levels preventing the detection of non-linear effects. A unique area in Iceland, where soil temperatures have recently increased due to geothermic activity, created a stable warming gradient in both grassland (dominated by Agrostis capillaris) and forest (Picea sitchensis) vegetation. By sampling soils which had been subjected to four years of temperature elevation (ambient (MAT 5.2 degrees C) to +40 degrees C), we investigated the shape of the response of soil bacterial communities to warming, and their associated community temperature adaptation. We used 16S rRNA amplicon sequencing to profile bacterial communities, and bacterial growth-based assays (3H-Leu incor-poration) to characterize community adaptation using a temperature sensitivity index (SI, log (growth at 40 degrees C/ 4 degrees C)). Despite highly dissimilar bacterial community composition between the grassland and forest, they adapted similarly to warming. SI was 0.6 (equivalent to a minimum temperature for growth of between-6 and-7 degrees C) in both control plots. Both diversity and community composition, as well as SI, showed similar threshold dynamics along the soil temperature gradient. There were no significant changes up to soil warming of 6-9 degrees C above ambient, beyond which all indices shifted in parallel, with SI increasing from 0.6 to 1.5. The consistency of these responses provide evidence for an important role for temperature as a direct driver of bacterial community shifts along soil temperature gradients.